Development of an Eco-Art Therapy-Based Group Guidance Program “KANVAS ALAM” to Enhance Flourishing Among Undergraduate Education Students - Elwas Berdha Krismona; Citra Tectona Suryawati; Agus Tri Susilo; Lilla Maturizka Ayu Asfarina; Aradea Daffa El Haris; Pau Kee (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to develop KANVAS ALAM, an eco-art therapy-based group guidance program designed to enhance flourishing among undergraduate education students. Flourishing, rooted in Seligman's PERMA framework, refers to optimal well-being encompassing positive emotions, engagement, relationships, meaning, and accomplishment. Employing the ADDIE research and development model, this study proceeded through analysis, design, and development stages. A preliminary needs assessment involving 497 undergraduate education students revealed that 38% exhibited moderate to low flourishing levels, underscoring the need for targeted interventions. The KANVAS ALAM program was structured across three sessions aligned with flourishing dimensions: meaning in life, social connectedness, and optimism about the future. Each session integrates nature-based creative activities, including drawing, mandala creation, and collage techniques. Expert validation was conducted by four specialists in guidance and counseling and art, who evaluated program components including rationale, needs analysis, objectives, facilitator competencies, operational plans, and evaluation indicators. Results confirmed the program's feasibility with revisions recommended in facilitator training, activity processes, media utilization, and reflection components. KANVAS ALAM represents a novel contribution as the first structured intervention integrating eco-art therapy into group guidance services specifically targeting flourishing in educational settings. This innovation extends counseling services beyond problem-solving toward positive psychological development. Future research should examine program effectiveness through quasi-experimental designs and explore long-term impacts on student well-being and academic outcomes. Keywords: group guidance, eco-art therapy, flourishing, student well-being, nature-based intervention